FINANCIAL DEEPENING AND ECONOMIC GROWTH IN NIGERIA: AN EMPIRICAL INVESTIGATION - Okoebor, Sylvester Ebosetale (African Journal of Social and Behavioural Sciences, 2021)
This study investigated the effects of financial deepening on economic growth in Nigeria. An empirical review of relevant literature shows a corresponding interaction between key economic variables that has the ability to exert effort on the policies of government to target major indicators that drives growth. The essential variables for this study are Per Capital Income, Broad Money Supply, Private Sector Credit, Financial Savings and Inflation. Secondary data were sourced from the Central Bank of Nigeria and World Bank from a scope of 1981 to 2018 for this work. The study adopted statistical analysis of Ordinary Least Square Regression method, supported with Unit Root, Heterocedasticity, Vector Error Correction Mechanism, Descriptive, Johansson Co-integration, and Correlation Matrix to test the stationarity, normality and long run relationships between variables. Some of the variables show significant influence on economic growth from the analysis thereby, giving credence to positive relationship between financial deepening and economic growth. Findings indicated that, the ratio of money supply to Gross Domestic Product has positive significant effects on per capita income. Inflation on the other hand has a negative significant influence on per capital income both at the short and longrun, while financial savings and private sector credit to Gross Domestic Product has insignificant negative and positive relationship with per capita income in the short-run respectively. These results support supply leading and demand following hypotheses theories that suggest financial deepening triggers economic growth. The implication of the study shall provide a sound financial deepening road map to economic policy makers; enhancing all inclusive financial development through Government fiscal and monetary policy measures. It will give a better understanding of the working dynamics of macroeconomic variables that has the ability to influence the economic well being of the citizens. The study recommended that, Government should implement flexible economic policies to enhance broad base financial market development to increase liquid and non liquid monetary instruments. Financial regulatory authorities should use inflation targeting tool instrument as financial deepening fiscal policy measure. Economic policy managers should institute a flexible financial inclusion policy frame work to drive effective financial savings dominance on economic growth